Examining the drivers of agricultural experimentation among smallholder farmers in Malawi - Hockett, M.; Richardson, Robert (Cambridge University Press, 2018)
Smallholder farmers in Malawi are faced with the challenge of managing complex and dynamic farming systems while also adapting to change within volatile agroecological conditions. Moreover, management decisions are influenced by a combination of local knowledge, expert recommendations and on-farm experimentation. Although many smallholder farmers actively experiment with new crops and technologies, little is known about the prevalence of experimentation or the types of experiments farmers conduct. This study examined the decision-making processes of experimenting farmers to explore the drivers of on-farm experimentation. Using a mixed-methods design that incorporated field observations, survey data and in-depth interviews, we identified numerous examples of experiments with new crops, varieties and techniques that had been executed either independently or through participation in an agricultural development project. Results of quantitative and qualitative analysis reveal that smallholder farmers in Malawi across a range of socioeconomic characteristics are inclined to experiment, and gender roles in agricultural experimentation vary widely. While experimental methods differ between farmers, there are commonalities in the drivers of experimentation, including adapting to climate change, improving soil health, improving nutrition and generating income. Smallholders have a great capacity for experimentation, and their knowledge, experience, preferences and priorities – if properly understood and incorporated – could ultimately benefit both future agricultural development projects and their participants.